(untitled) (Asian Journal of Pharmaceutics (AJP), 2025)
Tobacco harm reduction (THR) is an approach aimed at diminishing the adverse health effects of tobacco use by offering alternatives to combusted products. While complete abstinence remains the ideal outcome, a comprehensive understanding of THR may accelerate smoking reduction. This paper explores the role of THR in reducing smoking prevalence, its potential benefits, limitations, and concerns regarding public health impact. A narrative review of available literature and historical evidence was conducted to examine the principles of THR, its implications for smokers unable or unwilling to quit, and the associated ethical and public health considerations. Evidence suggests that absolute bans often promote black markets and illicit cigarette trade. For smokers who cannot achieve cessation, safer nicotine delivery alternatives may reduce morbidity and mortality. However, concerns exist about potential undermining of tobacco prevention efforts, particularly among adolescents, as well as the risk of widespread uptake among non-smokers. In addition, as alternative nicotine products are primarily manufactured by the tobacco industry, commercial interests strongly influence their promotion. THR may be considered at the individual level only when complete cessation is unachievable. Its use in tobacco control should be restricted to high-risk smokers, while safeguarding against the proliferation of nicotine use among non-smokers.